2011
DOI: 10.1002/ejoc.201100673
|View full text |Cite
|
Sign up to set email alerts
|

Second Generation Calix[6]trenamides – Highly Selective Graftable Receptors for Neutral Guests and Contact Ion Pairs

Abstract: With the aim of designing graftable calix[6]tren‐based receptors, calix[6]trenamides decorated with an appended functional arm were synthesized through [1+1] macrocyclization reactions between calix[6]trisamines and NTA‐lysine derivatives. NMR spectroscopy and ESI‐MS studies showed that one of these calix[6]trenamides, 5, behaves as a unique heteroditopic receptor towards charged or neutral species. Notably, it can selectively bind contact ammonium fluoride salts through a highly cooperative process. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…To this aim, we used a monofunctionalized calix[6]­tren amide precursor ( 1 ) that was recently reported by some of us (Scheme ). Reduction of the amido and carbamate groups of 1 with BH 3 ·THF led to the corresponding monofunctionalized calix[6]­tren ( 2 ) in 79% yield. To obtain a derivative that could be grafted through a CuAAC “click” reaction, an azide function was then introduced at the level of the appending arm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this aim, we used a monofunctionalized calix[6]­tren amide precursor ( 1 ) that was recently reported by some of us (Scheme ). Reduction of the amido and carbamate groups of 1 with BH 3 ·THF led to the corresponding monofunctionalized calix[6]­tren ( 2 ) in 79% yield. To obtain a derivative that could be grafted through a CuAAC “click” reaction, an azide function was then introduced at the level of the appending arm.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 1 and N -dansyl-1,6-hexanediamine were prepared according to procedures previously described in the literature. , All reactions were conducted under an inert atmosphere.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Aiming at mimicking the binding behavior of enzymes, several aqueous and water soluble synthetic receptors possessing more or less open aromatic cavities with converging polar groups have been reported by the groups of Davis,68 Jiang,911 and Jabin,12,13 among others. The obtained binding results demonstrated that the combination of a functionalized aromatic cavity (binding site with a low dielectric constant) displaying multiple open portals (cages or tubes) with converging polar groups is a successful strategy for achieving effective binding of neutral polar molecules in aqueous media and water with synthetic receptors (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of p -methyl substituents in the meso -phenyl groups of the receptors aimed at increasing the depth of their aromatic cavities. We employed pyridinium groups as water-solubilizing units, based on their performance for solubilizing related resorcinarene derived cavitands in water 11,13,22. We located the water solubilizing groups at the lower rim of the receptors, distal from the polar aromatic binding site.…”
Section: Introductionmentioning
confidence: 99%
“…The design and application of ion-pair receptors, capable of the simultaneous coordination of both anionic and cationic guest species, has attracted significant interest because of their potential application as novel extraction reagents for the purification of pernicious substances in the environment. Recently, this exciting area of ion-pair recognition has been concerned with the syntheses of host molecules that comprise binding sites for both anionic and cationic guests . Calixcrowns make up a family of calixarenes that exhibit a superior recognition of ion pairs via the cooperation of both the calixarene and crown moieties. , Beer and co-workers synthesized calixcrowns with binding sites for both anionic and cationic guest species as ion-pair receptors. ,, …”
mentioning
confidence: 99%